EEEP 2019
DOI: 10.32006/eeep.2019.1.5462
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study for the Characterization of Biogas Production From Cow Dung and Droppings

Abstract: The present work is an account of an ongoing work on biogas production from animal wastes at LEREA (Laboratoire d’enseignement et de recherche en énergétique appliquée) in Mamou, Guinea. The work consists of biogas production from anaerobic digestion and co-digestion of cow dung and droppings. We focus in this report on the determination of the physico-chemical characteristics of the experimental setup. We have carried out three experiments of anaerobic digestion each one lasting 45 days at mesophilic temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Usman et al (2019) found that poultry waste had 90.38±0.03% of DM, whereas the DM of rabbit manure varied from 72.8 -73.4% (Asiegbu and Oikeh, 1995). The DM of cow dung was 57% (Moussa Baldé et al, 2019). The previous references showed that the DM of chicken manure is higher than that of other animal waste.…”
Section: Discussionmentioning
confidence: 98%
“…Usman et al (2019) found that poultry waste had 90.38±0.03% of DM, whereas the DM of rabbit manure varied from 72.8 -73.4% (Asiegbu and Oikeh, 1995). The DM of cow dung was 57% (Moussa Baldé et al, 2019). The previous references showed that the DM of chicken manure is higher than that of other animal waste.…”
Section: Discussionmentioning
confidence: 98%